Misdiagnosed case of transthyretin amyloidosis in a fully investigated patient - E. S. Naumova; S. S. Nikitin; T. A. Adyan; D. S. Druzhinin; V. A. Varshavskiy (Нервно-мышечные болезни)
The DNA analysis revealed a transthyretin amyloidosis with a rare Phe53Leu mutation in a woman of 62 y.o. with the late onset progressive generalized axonal sensomotor neuropathy, dry eye syndrome, and an episode of severe unintentionally weight loss. The same mutation was found in her healthy 34 y.o. son, but not in a 42 y.o. daughter. The Congo red staining were negative in nerve and salivar gland biopsies samples. The reassessment of the transthyretin amyloidosis “red flags” showed that the patient fulfilled the criteria of the disease and the absence of amyloid deposition was not the ground to reject the hereditary cause of the condition. The reasons of the misdiagnosis are discussed.